MUTTAQIN AND IMAM CONCEPT IN AL-QUR’AN SURAT AL-FURQON VERSE 74 PERSPECTIVE - Tharaba, Fahim (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The first goal of Islamic education is started by family’s choice (education). In this case, Islam lines the goal of Islamic education by hadis Rasulullah SAW., ت نكحوا المراة لأربع لمالها ولجمالها ولنسابها ولدينها فظفر فى ذات الدين if it is taken to the education field, selected education are: (1)  لمالها ( full facility), (2)  لجمالها ( vision and mission), (3)  لنسابها ( al-Qur’an and sunnah, ect). and (4)  لدینها ( exact aqidah). Then, the education is directed to create ( ذریة قرة اعین) which can be done by pra, basic and middle education. Then, ( متقین ), it is directed to achieve ( متقین ) degree. And it is completed by bachelor education (S-1/Sarjana), and also graduate education (S-2/Magister) and the highest position is ( امام ) which can be completed by postgraduate education (S-3/Doktor). Finaly ( امام) status is completed by Profesor degree in each profession. There are so many arguments about Muttaqin and Imam, in this research, the author tries to discover and analyze by perspective of al-Qur’an especially surah al-Furqon verse 74.